On the use of the metallic nozzle of a cutting arc torch as a Langmuir probe. - Prevosto, Leandro; Kelly, Héctor; Mancinelli, Beatriz (My University, 2008)
The region inside the nozzle (bore diameter ≈1 mm) of a cutting arc torch is inaccessible to most plasma diagnostics, and numerical simulations are the only means to find out the relative importance of several physical processes. In this work, a study of electrostatic (Langmuir) probes applied to the inside of a high energy density 30 A cutting arc torch nozzle is presented. The metallic nozzle was used as a Langmuir probe, so the plasma flow is not perturbed by the probe as a solid body. Biasing the nozzle through an electric circuit that employs appropriate resistors together with the arc power source, the i–V nozzle characteristic was built. It was found that under a large positively biased nozzle, the electron current drained from the arc was relatively small, ≈1 A, notwithstanding the fact that the size of the nozzle was relatively large. On the other hand, an almost linear ion current was found for the ion branch for nozzle voltages well below the floating value. Based on the magnitude of inverse slope of the ion current, an estimation of the average electron temperature of the plasma in the vicinity of the nozzle wall was estimated from an ion sheath resistance model using a non-equilibrium two-temperature Saha-equation. An average electron temperature of about 4200 K and a corresponding plasma density of 4 × 1017 m−3 were found.La región dentro de la boquilla (diámetro del orificio ≈1 mm) de una antorcha de arco de corte es inaccesible para la mayoría de los diagnósticos de plasma y las simulaciones numéricas son los únicos medios para averiguar la importancia de varios procesos físicos. En este trabajo se ha realizado un estudio de la electrostática (Langmuir) Se presentan sondas aplicadas al interior de una boquilla de soplete de arco de corte de 30 A de alta densidad de energía. La boquilla metálica se utilizó como sonda Langmuir, por lo que el flujo de plasma no se ve perturbado por el sonda como un cuerpo sólido. Sesgo la boquilla a través de un circuito eléctrico que emplea resistencias junto con la fuente de alimentación del arco, se construyó la característica de boquilla i-V. Se encontró que bajo una gran boquilla polarizada positivamente, la corriente de electrones drenada del arco era relativamente pequeño, ≈1 A, a pesar de que el tamaño de la boquilla era relativamente grande. Por otro lado, se encontró una corriente iónica casi lineal para la rama iónica de la boquilla, tensiones muy por debajo del valor flotante. Basado en la magnitud de la pendiente inversa del ion corriente, una estimación de la temperatura media de los electrones del plasma en las proximidades de la pared de la boquilla se estimó a partir de un modelo de resistencia de la vaina iónica utilizando una ecuación Saha de dos temperaturas. Se encontró una temperatura media de los electrones de unos 4200 K y una densidad de plasma correspondiente de 4 × 1017 m−3.
Keywords: Langmuir probe.; Plasma flow.; Cutting arc torch.; Sonda Langmuir.; Flujo de plasma.; Soplete de arco de corte.